2021
DOI: 10.1111/hex.13202
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of aquatic physiotherapy and health‐related quality of life among people with Parkinson’s disease

Abstract: Background Enablers for people with Parkinson's disease (PD) participating in aquatic physiotherapy have been identified, and exercise improves health‐related quality of life (HRQoL) but it is unclear whether all enablers and barriers for aquatic physiotherapy specific to the PD population have been explored. Objective To describe HRQoL in people with PD who have undertaken aquatic physiotherapy, and explore their perceptions and attitudes regarding the programme. Methods Twenty‐one participants who participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…This study investigated physiotherapists' current practice in using aquatic physiotherapy for people with PD. Only one third of our surveyed physiotherapists reported using aquatic physiotherapy in their treatment of people with PD, which suggests that this is not a well-utilised treatment modality despite recent evidence demonstrating that it might be (Neto et al, 2020;Terrens et al, 2020Terrens et al, , 2021Terrens et al, 2018). This study highlights several barriers to implementing aquatic physiotherapy in practice.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This study investigated physiotherapists' current practice in using aquatic physiotherapy for people with PD. Only one third of our surveyed physiotherapists reported using aquatic physiotherapy in their treatment of people with PD, which suggests that this is not a well-utilised treatment modality despite recent evidence demonstrating that it might be (Neto et al, 2020;Terrens et al, 2020Terrens et al, , 2021Terrens et al, 2018). This study highlights several barriers to implementing aquatic physiotherapy in practice.…”
Section: Discussionmentioning
confidence: 69%
“…Treatment choice by the patient on whether they wish to participate in exercises in an aquatic environment also has to be taken into account when considering physiotherapy management of this clientele. Several barriers to participating in aquatic physiotherapy from a patient's perspective have been identified previously, such as fatigue, and safety getting dressed and undressed (Terrens et al, 2021). The study by Terrens et al (2021) was nested within a larger study, and examined healthrelated quality of life and patient perceptions and experiences regarding aquatic physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis (20 studies, 2707 PwPD) published in 2020 concluded that people with PD have a worse quality of life than healthy controls [4]. Studies have reported that exercise programs have different effects on quality of life [35][36][37]. There are some researches in the literature demonstrating that LSVT-BIG treatment improves the quality of life [26,38], while some studies have reported no changes [23,39].…”
Section: Discussionmentioning
confidence: 99%
“…A disadvantage of physical therapy is that incorrect exercise can affect the abutment and its injury. This trend also includes the adaptation of kinesiotherapy to the aquatic environment, which is called hydrokinetic therapy and aims at rehabilitating patients with lower limb conditions and amputations, due to the multiple benefits of practicing in the water environment and taking advantage of materials, equipment and devices designed to be used in immersion [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%